Novel architecture of multiplier for Accuracy-scalable approximate computing (Indo-American Journal of Life Sciences and Biotechnology, 2022)
Many error-tolerant applications rely on multiplication as a fundamental function.Approximate multiplication is regarded as an efficient method for balancing performance and accuracyagainst energy consumption. As a result, this research presents a low-power and compact multiplier foraccurate, scalable approximate computation. A carry-maskable adder and an approximate treecompressor (ATC) make up the proposed approximate multiplier (CMA). By adopting a simple circuittopology and a simple carry-masking technique, ATC compresses partial products while the CMAprovides precision scaling. This approximate multiplier reduces both power consumption and circuitarea when compared to the Wallace tree multiplier, according to the experimental designs.